Preparation method of core-shell nanofiber gas-sensitive material based on platinum-doped cobalt oxide and tin oxide heterostructure
By preparing core-shell nanofiber gas-sensitive materials based on platinum-doped cobalt-tin oxide heterostructure, the problem of low response value of hydrogen sulfide gas-sensitive materials in the prior art at room temperature is solved, and the low concentration of hydrogen sulfide gas is achieved Fast detection and good cycle stability, suitable for environmental monitoring and industrial safety.
Patent Information
- Application Number
- CN202411632222.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-11-15
AI Technical Summary
The existing hydrogen sulfide gas-sensitive materials have high operating temperatures and low response values at room temperature, which limits their use in practical applications and makes it difficult to effectively detect low-concentration hydrogen sulfide gas.
Core-shell nanofiber gas-sensitive materials based on platinum-doped cobalt oxide tin oxide heterostructure were prepared by mixing chloroplatinic acid, cobalt nitrate and dimethylimidazole, electrospinning and calcining to form Pt-Co3O4 @SnO2 core-shell structure nanofibers, using the combined action of heterojunction and precious metals to improve gas-sensitive performance.
High sensitivity and rapid response to low-concentration hydrogen sulfide gases are achieved at room temperature, with short response time and short recovery time, showing good cycle stability, and are suitable for environmental monitoring and industrial-safe gas detection.
Smart Images

Figure CN119265749A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of gas sensor preparation, and in particular to a core-shell nanofiber gas-sensitive material based on a platinum-doped cobalt oxide-tin oxide heterostructure, a preparation method thereof, and an application thereof in low-concentration hydrogen sulfide detection at room temperature. Background Art
[0002] Hydrogen sulfide (H2S) gas is a toxic pollutant that degrades air quality and harms human health. Its presence in indoor and outdoor environments is considered a hazard. H2S is often produced and released through various human activities, mainly in oil / gas wells, crude oil refining, sulfur springs, coal pits, coal gasification plants, decomposition of sulfur-containing organic matter, and food processing industries. In addition, H2S is produced for a variety of purposes, such as organic sulfur synthesis, metallurgical operations, analysis, and catalytic applications. A H2S content of 10 ppm is considered harmful to organisms. Once the H2S concentration exceeds 10 ppm, it may cause coma, critical poisoning, personal pain, olfactory system failure, organ damage, and interfere with mitochondrial function. In addition, the current hydrogen sulfide gas-sensitive materials generally have high operating temperatures and low response values, which limits their application in practice. Therefore, the development of high-performance room-temperature hydrogen sulfide gas-sensitive materials is very necessary to ensure the safe use of hydrogen sulfide gas. Summary of the invention
[0003] The purpose of the present invention is to solve the above problems existing in the prior art and to provide a method for preparing a core-shell nanofiber gas-sensitive material based on a platinum-doped cobalt oxide-tin oxide heterostructure, which can effectively detect the concentration of hydrogen sulfide gas in the air of a workplace at room temperature.
[0004] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows: a method for preparing a core-shell nanofiber gas-sensitive material based on a platinum-doped cobalt oxide-tin oxide heterostructure comprises the following steps:
[0005] S1: mixing chloroplatinic acid solution, cobalt nitrate solution and dimethylimidazole solution, allowing to react, separating the precipitate from the solution, and obtaining Pt@ZIF-67 crystalline material;
[0006] S2: preparing a shell solution and a core solution; the shell solution is a mixture of a tin source, a polymer, and an organic solvent; the core solution is a mixture of a Pt@ZIF-67 crystal material, a polymer, and an organic solvent;
[0007] S3: adding the shell layer solution and the core layer solution prepared in S2 to a coaxial electrospinning device for coaxial electrospinning to obtain precursor nanofibers of a Pt-Co@Sn core-shell structure;
[0008] S4: calcining the Pt-Co@Sn core-shell structured precursor nanofibers in S3 to obtain Pt-Co3O4@SnO2 core-shell structured nanofibers.
[0009] Preferably, the solvent of the chloroplatinic acid solution in S1 is anhydrous ethanol; the solvent of the cobalt nitrate solution and the dimethylimidazole solution is methanol; the mass concentrations of the chloroplatinic acid solution, the cobalt nitrate solution and the dimethylimidazole solution are 9-11 g / L, 48-52 g / L and 24-26 g / L, respectively.
[0010] Preferably, the mass ratio of the tin source, the polymer and the organic solvent in S2 is 0.4-0.6:1.2-1.6:9-10; the mass ratio of the Pt@ZIF-67 crystal material, the polymer and the organic solvent is 0.2-0.3:0.4-0.5:4-5.
[0011] Preferably, the tin source in S2 is one or more of tin acetate, tin nitrate, stannous oxalate, tetraphenyltin, tetrabutyltin, tin dichloride and tin tetrachloride.
[0012] Preferably, the polymer in S2 is one or more of polyvinyl pyrrolidone, polyvinyl alcohol, polyvinyl nitrile, cellulose acetate and polyacrylonitrile.
[0013] More preferably, the organic solvent in S2 comprises N,N-dimethylformamide and tetrahydrofuran, and the volume ratio of N,N-dimethylformamide to tetrahydrofuran is 4:1.
[0014] Further preferably, in the coaxial electrospinning of S3, the shell and core layer solutions are prepared using 5 ml syringes, the shell solution syringe advancing speed is 0.004 mm / min, the core layer solution syringe advancing speed is 0.0025 mm / min, the applied voltage is 17-20 kV, and the ambient humidity is controlled at 45-55%.
[0015] More preferably, the calcination temperature in S4 is 500° C. and is kept at this temperature for 2 hours.
[0016] The present invention also provides a core-shell nanofiber gas-sensitive material based on a platinum-doped cobalt oxide and tin oxide heterostructure obtained by the above preparation method.
[0017] The present invention also provides the application of a core-shell nanofiber gas-sensitive material based on a platinum-doped cobalt oxide and tin oxide heterostructure in the detection of low-concentration hydrogen sulfide at room temperature.
[0018] In terms of the molecular structure design of gas-sensitive materials, the present invention adopts the method of constructing heterojunction, doping precious metals, metal organic framework derivatization, and coaxial electrospinning to prepare Pt-Co3O4@SnO2 core-shell structured nanofibers, which have the following advantages: First, due to the difference in the work functions of the two materials in the heterojunction, charge redistribution is required to achieve balance, which accelerates the movement of electrons, expands the thickness of the depletion layer, and improves the gas-sensitive performance; second, the introduction of precious metals promotes the dissociation of oxygen molecules due to the combined effects of electronic sensitization and chemical sensitization, produces more reactive chemically adsorbed oxygen ions, and then overflows on the surface of the metal oxide, reacts with more target gas molecules, causes the release of electrons, and leads to a rapid change in resistance, thereby significantly improving the gas sensing performance; third, the semiconductor metal oxide derived from the metal organic framework using MOF as a self-sacrificing template has regular internal pores, a large specific surface area, and open metal sites, which significantly enhances the gas-sensitive performance and has unique advantages in gas sensing.
[0019] In terms of the synthesis technology of gas-sensitive materials, ZIF-67 is a metal-organic framework material composed of cobalt ions and 2-methylimidazole ligands. ZIF-67 has a unique pore structure and can be effectively converted into cobalt tetroxide with a high specific surface area during heat treatment. During the calcination process, the organic components in ZIF-67 will decompose, and the metal cobalt will be converted into cobalt oxide (Co3O4) through oxidation, retaining the original porous structure of ZIF-67. This pore structure plays an important role in the adsorption and diffusion of gas molecules. Co3O4 and tin oxide (SnO2) form a heterojunction structure through interfacial reaction, which may include Co-O-Sn bonding. This interfacial bonding improves the charge transfer efficiency of the material and the stability of the heterostructure, which is beneficial to improve the sensitivity of gas sensing. The introduction of platinum significantly improves the surface catalytic activity of Co3O4 / SnO2 materials, prompting gas molecules to react faster on the surface of the material. The presence of platinum can also regulate the electronic structure of the material and improve the sensitivity and response speed of gas detection.
[0020] In terms of the specific preparation method of gas-sensitive materials, the coaxial electrospinning method can construct a core-shell structure at the nanoscale, and evenly distribute platinum-doped cobalt oxide in the outer shell of tin oxide. By adjusting the spinning parameters, the fiber diameter, core-shell ratio and platinum doping amount can be precisely controlled to optimize the gas-sensitive performance of the material. The design of the core-shell structure gives the material a heterojunction effect, which enhances the adsorption and charge transfer efficiency of gas molecules, thereby improving the sensitivity and selectivity to specific gases. At the same time, platinum doping further improves the surface activity of the material, reduces the operating temperature, and improves the response speed and repeatability. After the coaxial electrospinning is completed, the MOF organic template and polymer carrier still exist in the nanofibers. Through high-temperature calcination, these organic components can be completely removed, the skeleton structure of the inorganic oxide can be retained, and pure cobalt oxide and tin oxide can be formed. The calcination process will cause cobalt oxide and tin oxide to transform from an amorphous state to a crystalline state, significantly improving the stability and conductivity of the material. At the same time, by regulating the calcination temperature and time, the crystallinity and phase composition of the material can be optimized to achieve the best gas-sensitive performance. During the calcination process, the interface between the platinum-doped cobalt oxide and the tin oxide will further solidify, enhancing the stability of the heterostructure and ensuring the durability of the core-shell structure in practical applications. This step is crucial to ensure the long-term performance and reproducible response of the material.
[0021] The beneficial effects of the present invention are as follows: the present invention uses cobalt source, tin source, platinum source and high molecular polymer as raw materials, and prepares nano-scale platinum-doped cobalt oxide tin oxide gas-sensitive material Pt-Co3O4@SnO2 with high sensitivity and rapid response to hydrogen sulfide gas by coaxial electrospinning. The gas-sensitive material exhibits excellent gas-sensitive performance to H2S gas at room temperature, and the response value reaches 15800 at a H2S gas concentration of 200ppb, the response time is 47s, and the recovery time is 8s; it shows that it has excellent gas-sensitive performance, short response time, can quickly detect low-concentration H2S gas, and the recovery time is also short, showing good cycle stability. Therefore, the gas-sensitive material in the present invention has good sensitivity and stability, and can be widely used in the fields of environmental monitoring, industrial safety and gas sensors at room temperature for the detection of H2S gas. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The corresponding curves of Examples 1-4 and Comparative Examples 1-2 at room temperature for H2S with a gas concentration of 2 ppm.
[0023] Figure 2 The corresponding curves of Examples 1-4 and Comparative Examples 1-2 at room temperature for H2S with a gas concentration of 200 ppb. DETAILED DESCRIPTION
[0024] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments.
[0025] Example 1
[0026] (1) Preparation of Pt@ZIF-67 crystals: 6.56 g of dimethylimidazole and 5.82 g of cobalt nitrate hexahydrate were dissolved in 250 ml of methanol. The two solutions were then mixed with 10 ml of 10 g / L chloroplatinic acid solution and stirred for 2 h. The resulting solution was allowed to react at room temperature for 24 h to obtain Pt@ZIF-67 crystals, which were collected by centrifugation and dried for later use.
[0027] (2) Preparation of shell and core layer solutions: To prepare the shell solution, 0.6 g of tin tetrachloride pentahydrate and 1.5 g of polyacrylonitrile were dissolved in 10 mL of a mixed solvent of N,N-dimethylformamide and tetrahydrofuran (volume ratio of 4:1), and stirred until uniform and transparent to form a shell solution. To prepare the core layer solution, 0.4 g of dried Pt@ZIF-67 crystals and 1.0 g of polyacrylonitrile were dissolved in 10 mL of a mixed solvent of N,N-dimethylformamide and tetrahydrofuran (volume ratio of 4:1), and stirred evenly to form a core layer solution.
[0028] (3) Coaxial electrospinning: The prepared shell solution and core solution are injected into the coaxial electrospinning device using a 5 ml needle tube, with the shell solution needle tube advancing speed of 0.004 mm / min and the core solution needle tube advancing speed of 0.0025 mm / min. The voltage is controlled to be 18 kV, the collection distance is 15 cm, the collection device speed is 300 rpm, and the ambient humidity is controlled at 45-55%. Under this condition, spinning is performed to obtain Pt-Co@Sn core-shell structure precursor nanofibers.
[0029] (4) Calcination: The precursor nanofibers are heated to 500°C in an air atmosphere and kept at this temperature for 2 h to obtain Pt-Co3O4@SnO2 core-shell structure nanofibers, thus completing the preparation of the gas-sensitive material.
[0030] (5) Test sample preparation: The calcined powder sample was ground in a mortar and then dispersed in a small amount of ethanol. After ultrasonic centrifugation, the powder was deposited on a gold interdigital electrode and allowed to stand at room temperature until the ethanol evaporated completely. A gas sensor capable of detecting hydrogen sulfide was obtained.
[0031] Example 2
[0032] (1) Preparation of Pt@ZIF-67 crystals: 6.56 g of dimethylimidazole and 5.82 g of cobalt nitrate hexahydrate were dissolved in 250 ml of methanol. The two solutions were then mixed with 15 ml of 10 g / L chloroplatinic acid solution and stirred for 2 h. The resulting solution was allowed to react at room temperature for 24 h to obtain Pt@ZIF-67 crystals, which were collected by centrifugation and dried for later use.
[0033] (2) Preparation of shell and core layer solutions: To prepare the shell solution, 0.6 g of tin tetrachloride pentahydrate and 1.5 g of polyacrylonitrile were dissolved in 10 mL of a mixed solvent of N,N-dimethylformamide and tetrahydrofuran (volume ratio of 4:1), and stirred until uniform and transparent to form a shell solution. To prepare the core layer solution, 0.4 g of dried Pt@ZIF-67 crystals and 1.0 g of polyacrylonitrile were dissolved in 10 mL of a mixed solvent of N,N-dimethylformamide and tetrahydrofuran (volume ratio of 4:1), and stirred evenly to form a core layer solution.
[0034] (3) Coaxial electrospinning: The prepared shell solution and core solution are injected into the coaxial electrospinning device using a 5 ml needle tube, with the shell solution needle tube advancing speed of 0.004 mm / min and the core solution needle tube advancing speed of 0.0025 mm / min. The voltage is controlled to be 18 kV, the collection distance is 15 cm, the collection device speed is 300 rpm, and the ambient humidity is controlled at 45-55%. Under this condition, spinning is performed to obtain Pt-Co@Sn core-shell structure precursor nanofibers.
[0035] (4) Calcination: The precursor nanofibers are heated to 500°C in an air atmosphere and kept at this temperature for 2 h to obtain Pt-Co3O4@SnO2 core-shell structure nanofibers, thus completing the preparation of the gas-sensitive material.
[0036] (5) Test sample preparation: The calcined powder sample was ground in a mortar and then dispersed in a small amount of ethanol. After ultrasonic centrifugation, the powder was deposited on a gold interdigital electrode and allowed to stand at room temperature until the ethanol evaporated completely. A gas sensor capable of detecting hydrogen sulfide was obtained.
[0037] Example 3
[0038] (1) Preparation of Pt@ZIF-67 crystals: 6.56 g of dimethylimidazole and 5.82 g of cobalt nitrate hexahydrate were dissolved in 250 ml of methanol. The two solutions were then mixed with 20 ml of 10 g / L chloroplatinic acid solution and stirred for 2 h. The resulting solution was allowed to react at room temperature for 24 h to obtain Pt@ZIF-67 crystals, which were collected by centrifugation and dried for later use.
[0039] (2) Preparation of shell and core layer solutions: To prepare the shell solution, 0.6 g of tin tetrachloride pentahydrate and 1.5 g of polyacrylonitrile were dissolved in 10 mL of a mixed solvent of N,N-dimethylformamide and tetrahydrofuran (volume ratio of 4:1), and stirred until uniform and transparent to form a shell solution. To prepare the core layer solution, 0.4 g of dried Pt@ZIF-67 crystals and 1.0 g of polyacrylonitrile were dissolved in 10 mL of a mixed solvent of N,N-dimethylformamide and tetrahydrofuran (volume ratio of 4:1), and stirred evenly to form a core layer solution.
[0040] (3) Coaxial electrospinning: The prepared shell solution and core solution are injected into the coaxial electrospinning device using a 5 ml needle tube, with the shell solution needle tube advancing speed of 0.004 mm / min and the core solution needle tube advancing speed of 0.0025 mm / min. The voltage is controlled to be 18 kV, the collection distance is 15 cm, the collection device speed is 300 rpm, and the ambient humidity is controlled at 45-55%. Under this condition, spinning is performed to obtain Pt-Co@Sn core-shell structure precursor nanofibers.
[0041] (4) Calcination: The precursor nanofibers are heated to 500°C in an air atmosphere and kept at this temperature for 2 h to obtain Pt-Co3O4@SnO2 core-shell structure nanofibers, thus completing the preparation of the gas-sensitive material.
[0042] (5) Test sample preparation: The calcined powder sample was ground in a mortar and then dispersed in a small amount of ethanol. After ultrasonic centrifugation, the powder was deposited on a gold interdigital electrode and allowed to stand at room temperature until the ethanol evaporated completely. A gas sensor capable of detecting hydrogen sulfide was obtained.
[0043] Example 4
[0044] (1) Preparation of Pt@ZIF-67 crystals: 6.56 g of dimethylimidazole and 5.82 g of cobalt nitrate hexahydrate were dissolved in 250 ml of methanol. The two solutions were then mixed with 20 ml of 10 g / L chloroplatinic acid solution and stirred for 2 h. The resulting solution was allowed to react at room temperature for 24 h to obtain Pt@ZIF-67 crystals, which were collected by centrifugation and dried for later use.
[0045] (2) Preparation of shell and core layer solutions: To prepare the shell solution, 0.6 g of tin tetrachloride pentahydrate and 1.5 g of polyacrylonitrile were dissolved in 10 mL of a mixed solvent of N,N-dimethylformamide and tetrahydrofuran (volume ratio of 4:1), and stirred until uniform and transparent to form a shell solution. To prepare the core layer solution, 0.4 g of dried Pt@ZIF-67 crystals and 1.0 g of polyacrylonitrile were dissolved in 10 mL of a mixed solvent of N,N-dimethylformamide and tetrahydrofuran (volume ratio of 4:1), and stirred evenly to form a core layer solution.
[0046] (3) Coaxial electrospinning: The prepared shell solution and core solution are injected into the coaxial electrospinning device using a 5 ml needle tube, with the shell solution needle tube advancing speed of 0.004 mm / min and the core solution needle tube advancing speed of 0.0025 mm / min. The voltage is controlled to be 18 kV, the collection distance is 15 cm, the collection device speed is 300 rpm, and the ambient humidity is controlled at 45-55%. Under this condition, spinning is performed to obtain Pt-Co@Sn core-shell structure precursor nanofibers.
[0047] (4) Calcination: The precursor nanofibers are heated to 500°C in an air atmosphere and kept at this temperature for 2 h to obtain Pt-Co3O4@SnO2 core-shell structure nanofibers, thus completing the preparation of the gas-sensitive material.
[0048] (5) Test sample preparation: The calcined powder sample was ground in a mortar and then dispersed in a small amount of ethanol. After ultrasonic centrifugation, the powder was deposited on a gold interdigital electrode and allowed to stand at room temperature until the ethanol evaporated completely. A gas sensor capable of detecting hydrogen sulfide was obtained.
[0049] Comparative Example 1
[0050] (1) Preparation of ZIF-67 crystals: 6.56 g of dimethylimidazole and 5.82 g of cobalt nitrate hexahydrate were dissolved in 250 ml of methanol, respectively. The two solutions were mixed and stirred for 2 h. The resulting solution was allowed to react at room temperature for 24 h to obtain ZIF-67 crystals, which were collected by centrifugation and dried for later use.
[0051] (2) Preparation of spinning solution: 0.4 g of dried ZIF-67 crystals and 1.0 g of polyacrylonitrile were dissolved in 10 mL of a mixed solvent of N,N-dimethylformamide and tetrahydrofuran (volume ratio of 4:1), and stirred evenly to form a spinning solution.
[0052] (3) Electrospinning: The prepared solution was placed in a 5 ml needle tube, the needle tube propulsion speed was 0.004 mm / min, the control voltage was 18 kV, the collection distance was 15 cm, the collection device speed was 300 rpm, and the ambient humidity was controlled at 45-55%. Under these conditions, ZIF-67 / PAN precursor nanofibers were obtained.
[0053] (4) Calcination: The precursor nanofibers are heated to 500°C in an air atmosphere and kept at this temperature for 2 h to obtain Co3O4 nanofibers, thus completing the preparation of the MOF-derived Co3O4 gas-sensitive material.
[0054] (5) Test sample preparation: The calcined powder sample was ground in a mortar and then dispersed in a small amount of ethanol. After ultrasonic centrifugation, the powder was deposited on a gold interdigital electrode and allowed to stand at room temperature until the ethanol evaporated completely. A gas sensor capable of detecting hydrogen sulfide was obtained.
[0055] Comparative Example 2
[0056] (1) Preparation of ZIF-67 crystals: 6.56 g of dimethylimidazole and 5.82 g of cobalt nitrate hexahydrate were dissolved in 250 ml of methanol, respectively. The two solutions were mixed and stirred for 2 h. The resulting solution was allowed to react at room temperature for 24 h to obtain ZIF-67 crystals, which were collected by centrifugation and dried for later use.
[0057] (2) Preparation of shell and core layer solutions: To prepare the shell solution, 0.6 g of tin tetrachloride pentahydrate and 1.5 g of polyacrylonitrile were dissolved in 10 mL of a mixed solvent of N,N-dimethylformamide and tetrahydrofuran (volume ratio of 4:1), and stirred until uniform and transparent to form a shell solution. To prepare the core layer solution, 0.4 g of dried ZIF-67 crystals and 1.0 g of polyacrylonitrile were dissolved in 10 mL of a mixed solvent of N,N-dimethylformamide and tetrahydrofuran (volume ratio of 4:1), and stirred evenly to form a core layer solution.
[0058] (3) Coaxial electrospinning: The prepared shell solution and core solution are injected into the coaxial electrospinning device using a 5 ml needle tube, with the needle tube pushing speed of the shell solution at 0.004 mm / min and the needle tube pushing speed of the core solution at 0.0025 mm / min. The voltage is controlled to be 18 kV, the collection distance is 15 cm, the collection device speed is 300 rpm, and the ambient humidity is controlled at 45-55%. Spinning under these conditions, Co@Sn core-shell structure precursor nanofibers are obtained.
[0059] (4) Calcination: The precursor nanofibers are heated to 500°C in an air atmosphere and kept at this temperature for 2 h to obtain Co3O4@SnO2 core-shell structure nanofibers, thus completing the preparation of the gas-sensitive material.
[0060] (5) Test sample preparation: The calcined powder sample was ground in a mortar and then dispersed in a small amount of ethanol. After ultrasonic centrifugation, the powder was deposited on a gold interdigital electrode and allowed to stand at room temperature until the ethanol evaporated completely. A gas sensor capable of detecting hydrogen sulfide was obtained.
[0061] The gas sensing performance of the gas sensors prepared in Examples 1-4 and Comparative Examples 1-2 to H2S of different concentrations at room temperature was tested. The test results are shown in Table 1.
[0062] Table 1 Gas sensing performance of different nanomaterial sensors to different concentrations of H2S at room temperature
[0063]
[0064] The response time and recovery time are the time taken to reach 90% of the maximum response and recovery respectively.
[0065] It can be seen from Table 1: First, the response values of Examples 1-4 are significantly higher than those of the comparative examples, especially the response value of Example 2 at a H2S gas concentration of 200ppb reaches 15800, indicating that its gas-sensitive performance is superior. This shows that the Pt-Co3O4@SnO2 structure has good performance in terms of sensitivity to H2S gas. The response time is generally short, with the shortest being 47s in Example 2, indicating that the material has advantages in rapid detection. The recovery time is also maintained in a short range, usually 6-8s, showing good cyclic stability. The presence of Pt may further enhance the catalytic activity of the material, help accelerate the oxidation reaction of H2S, and thus improve the response speed and response value, proving that the prepared Pt-Co3O4@SnO2 core-shell structure nanofibers can well detect low concentrations (200ppb) of H2S gas, and have significant use value.
[0066] Second, Comparative Example 2 has significant improvements in response value and reaction speed compared with Comparative Example 1, reflecting certain optimization in material design. Although neither of them has reached the gas-sensing performance level of the embodiment, Comparative Example 2 shows better potential. This is because the design of the core-shell structure can effectively increase the specific surface area of the material, thereby increasing the contact area between the gas molecules and the material, promoting gas adsorption and reaction, and enhancing the sensitivity of the sensor. The improvement of Comparative Example 2 enables it to have certain gas-sensing capabilities in certain applications, while Comparative Example 1 has almost no practical application value. There is still room for improvement in the structural optimization of Comparative Example 2 to further enhance the gas-sensing performance.
[0067] Third, Example 2 exhibits the best gas-sensing performance, but as the amount of Pt added increases, the gas-sensing performance of Examples 3 and 4 shows a downward trend. This is because when the Pt content is too high, it may lead to saturation of the catalytic sites, making it impossible for gas molecules to be effectively adsorbed, but limiting the reaction rate. Too much Pt may cause agglomeration between particles, reduce the effective specific surface area, and reduce the overall gas-sensing performance of the material.
[0068] In summary, the gas-sensitive material Pt-Co3O4@SnO2 prepared by the present invention exhibits excellent gas-sensitive performance to H2S gas at room temperature, has a short response time, can quickly detect low-concentration H2S gas, and has a short recovery time, showing good cycle stability. Therefore, the gas-sensitive material in the present invention has good sensitivity and stability, and can be widely used in the fields of environmental monitoring, industrial safety, and gas sensors at room temperature to detect H2S gas.
[0069] The specification and drawings of the present invention are considered to be illustrative rather than restrictive. On the basis of the present invention, those skilled in the art can make some substitutions and modifications to some of the technical features according to the disclosed technical content without creative labor, all of which are within the protection scope of the present invention.
Claims
1. A method for preparing a core-shell nanofiber gas-sensitive material based on a platinum-doped cobalt oxide and tin oxide heterostructure, characterized in that: The following steps are involved: S1: mixing chloroplatinic acid solution, cobalt nitrate solution and dimethylimidazole solution, allowing to react, separating the precipitate from the solution, and obtaining Pt@ZIF-67 crystalline material; S2: preparing a shell solution and a core solution; the shell solution is a mixture of a tin source, a polymer, and an organic solvent; the core solution is a mixture of a Pt@ZIF-67 crystal material, a polymer, and an organic solvent; S3: adding the shell layer solution and the core layer solution prepared in S2 to a coaxial electrospinning device for coaxial electrospinning to obtain precursor nanofibers of a Pt-Co@Sn core-shell structure; S4: calcining the Pt-Co@Sn core-shell structured precursor nanofibers in S3 to obtain Pt-Co3O4@SnO2 core-shell structured nanofibers.
2. The preparation method according to claim 1, characterized in that: The solvent of the chloroplatinic acid solution in S1 is anhydrous ethanol; the solvents of the cobalt nitrate solution and the dimethylimidazole solution are methanol; the mass concentrations of the chloroplatinic acid solution, the cobalt nitrate solution, and the dimethylimidazole solution are 9-11 g / L, 48-52 g / L, and 24-26 g / L, respectively.
3. The preparation method according to claim 1, characterized in that: The mass ratio of the tin source, the polymer, and the organic solvent in S2 is 0.4-0.6:1.2-1.6:9-10; the mass ratio of the Pt@ZIF-67 crystal material, the polymer, and the organic solvent is 0.2-0.3:0.4-0.5:4-5.
4. The preparation method according to claim 1, characterized in that: The tin source in S2 is one or more of tin acetate, tin nitrate, stannous oxalate, tetraphenyltin, tetrabutyltin, tin dichloride, and tin tetrachloride.
5. The preparation method according to claim 1, characterized in that: The polymer in S2 is one or more of polyvinyl pyrrolidone, polyvinyl alcohol, polyvinyl nitrile, cellulose acetate and polyacrylonitrile.
6. The preparation method according to claim 1, characterized in that: The organic solvent in S2 includes N,N-dimethylformamide and tetrahydrofuran, and the volume ratio of N,N-dimethylformamide to tetrahydrofuran is 4:
1.
7. The preparation method according to claim 1, characterized in that: In the coaxial electrospinning of S3, the shell and core layer solutions are prepared using 5 ml syringes, the shell solution syringe advancing speed is 0.004 mm / min, the core layer solution syringe advancing speed is 0.0025 mm / min, the applied voltage is 17-20 kV, and the environmental humidity is controlled at 45-55%.
8. The preparation method according to claim 1, characterized in that: The calcination temperature in S4 is 500° C. and is kept at this temperature for 2 hours.
9. A core-shell nanofiber gas-sensitive material based on a platinum-doped cobalt oxide and tin oxide heterostructure obtained by the preparation method according to any one of claims 1 to 8.
10. Use of the core-shell nanofiber gas-sensitive material based on platinum-doped cobalt oxide and tin oxide heterostructure as claimed in claim 9 in the detection of low-concentration hydrogen sulfide at room temperature.
Citation Information
Patent Citations
Chain bead-shaped tin oxide-based heterogeneous nanofiber gas-sensitive material as well as preparation and application thereof
CN115262034A
Preparation method of PdPt / SnO2 (at) ZIF-8 gas-sensitive composite material and hydrogen sensing application of PdPt / SnO2 (at) ZIF-8 gas-sensitive composite material
CN117054492A
Preparation method and gas-sensitive application of Co3O4 nanocube embedded ZnO nanofiber tube
CN118005067A